Pengaruh Self Regulated Learning dan Parent Involvement terhadap Student Engagement dalam Pembelajaran Jarak Jauh Selama Pandemi Covid-19 - Zulfa Indira Wahyuni (Humanitas (Jurnal Psikologi), 2022)
Online learning during the Covid-19 pandemic has reduced student engagement in learning. In fact, students will have good achievements and online learning will be effective when students engage in learning. The purpose of this study was to find out the factors that influence students engagement in online learning among junior high school students. The variables used in this study are self-regulated learning and parent involvement. The study used a quantitative approach involving 295 junior high school students who did online learning. Sampling was taken by convenience sampling technique. The measuring instrument used was the student engagement scale in online school, the scale from Toering et al (2012) and the Parental Involvement Mechanism Measurement. Based on the results of hypothesis testing, the first conclusion is that there is a significant relation between self-regulated learning & parent involvement and student engagement in online learning. Furthermore, the variables with significant coefficient values are planning, efforts and self-efficacy. Based on study results, teachers are suggested to provide explanation and insight for students so that students can have a plan in doing assignments. For students, it is advisable to put more efforts into understanding the lessons and discipline in doing assignments so that they are more attached to the school.